Polymorphisms of the human Y chromosome in populations from northern Peru - Carbajal-Caballero, Néstor (2005)
The non-recombination region of the human Y chromosome is a very informative genetic tool for unraveling the history of human populations. 105 individuals from four northern populations of Peru, were genotyped for three Y-specific loci: DYS287, DYS199 and DYS390. Only one individual carried the YAP+ /C lineage, more probably of African origin. The highest frequency of Amerindian Y chromosomes, represented by the YAP- / T lineage, was found in the Aguaruna population of Yamayakat (97%), decreasing gradually in the mestizo population of Moche (73%), Santiago de Chuco (53%) and Trujillo (33%); on the other hand, the admixture level was higher in north-western populations. The most frequent haplotypes were YAP- /C/24 in Trujillo (47%) and YAP- /T/24 in Santiago de Chuco (23%). The haplotype diversity was higher in Santiago de Chuco (0,881) than in Trujillo (0,752). It stands out in the proportions of Amerindian Y chromosomes within Peruvian populations in spite of more than 500 years of influence of Hispanic and other cultures.